THE CREATION OF SHORT STORY CHARACTER THROUGH WAYANG GOLEK PUPPET SHOW - Nita Hermiyati; Euis Eti Rohaeti; Ika Mustika (JLER (Journal of Language Education Research), 2021)
Writing short text requires the ability to cultivate the imagination to pour it into writing that is animate and interesting. In fact, creating imagination is not easy, therefore we need media that can help the process of getting ideas and generating students' interest in learning the short text. This research will use video wayang golek as a means to create characters according to the characters in the wayang golek play. The essence of this research is the achievement of students in determining interesting wayang golek figures and made according to personal imagination by imitating directly, modifying, or even changing the whole according to personal desires. The characters in wayang stories that are considered regionally will be packaged to be more interesting and modern according to the imagination a teenager. Data were analyzed using descriptive qualitative conducted in three stages, reading short stories, analyzing character characters, and describing character characters created from wayang golek. The results of the analysis show that the use of wayang golek media can improve students' abilities in creating character characters so as to create a short story text that has its own attractiveness, inherit adolescent imagination and thought, and can preserve the cultural richness of the West Java region. This wayang golek can also be used by teachers as an effective medium in learning. Students will find interesting parts and create their own character so as to create a process of independence in learning. and describe the characters created by wayang golek. The results of the analysis show that the use of wayang golek media can improve students' abilities in creating character characters so as to create a short story text that has its own attractiveness, inherit adolescent imagination and thought, and can preserve the cultural richness of the West Java region. This wayang golek can also be used by teachers as an effective medium in learning. Students will find interesting parts and create their own character so as to create a process of independence in learning. and describe the characters created by wayang golek. The results of the analysis show that the use of wayang golek media can improve students' abilities in creating character characters so as to create a short story text that has its own attractiveness, inherit adolescent imagination and thought, and can preserve the cultural richness of the West Java region. This wayang golek can also be used by teachers as an effective medium in learning. Students will find interesting parts and create their own character so as to create a process of independence in learning. inherit the imagination and thoughts of adolescents, and can preserve the cultural wealth of the West Java region. This wayang golek can also be used by teachers as an effective medium in learning. Students will find interesting parts and create their own character so as to create a process of independence in learning. inherit the imagination and thoughts of adolescents, and can preserve the cultural richness of the area of West Java. This wayang golek can also be used by teachers as an effective medium in learning. Students will find interesting parts and create their own character so as to create a process of independence in learning.